Teachers’ Perception towards Continuous and Comprehensive Evaluation (CCE) at Secondary Schools of Lakhimpur District of Assam - Mondal, Mithun; Doley, Jayanta (International Journal of Psychosocial Rehabilitation, 2020)
Evaluation not only involves gathering and interpreting information about how well an educational program is succeeding in attaining its objectives but also judgments about the goals themselves. It involves questions about how well a program is helping to meet larger educational goals and gives feedback to the process with a view to some actions to increase the effectiveness, efficiency, etc. Educational evaluation is clearly decision-oriented and is undertaken with the intention that some action will take place as a result. It is intended to lead to better policies and practices in education. The Continuous and Comprehensive Evaluation is one of the innovative schemes of evaluation implemented by the Central Board of Secondary Education (CBSE) under the RTE Act-2009 in India. Continuous and Comprehensive Evaluation (CCE) refers to a system of school-based evaluation of students that includes all aspects of students’ development. Major objectives of this study were (i) to find out the perception of secondary school teachers towards Continuous and Comprehensive Evaluation (CCE) in Lakhimpur District of Assam; (ii) to find out the difference between the male and female secondary school teachers’ perception towards Continuous and Comprehensive Evaluation (CCE) in Lakhimpur District of Assam; and (iii) to find out the difference between the rural and urban secondary school teachers’ perception towards Continuous and Comprehensive Evaluation (CCE) in Lakhimpur District of Assam. In this piece of research, the investigators used the descriptive cum survey method of educational research in order to find out the perception of secondary school teachers towards Continuous and Comprehensive Evaluation (CCE) in the Lakhimpur District of Assam. The researcher found that the secondary school teachers of the Lakhimpur District of Assam had shown positive perception towards CCE. The researcher has also found that the male-female and rural-urban secondary school teachers do not differ significantly in terms of their level of perception towards CCE.